Removal of Residual oil in palm oil mill effluent (pome) by using non-ionic surfactan - Nuuraishah, Binti Zilini (Universiti Malaysia Sarawak, UNIMAS, 2013)
Palm oil mill effluent (POME) wastewater sample was used to study the removal of its residual oil by using non-ionic surfactant. POME has been identified as oily wastewater because it contains high amount of organic contaminants and residual oil. The production of POME and its untreated discharge into the river causes water pollution and affects the survival of aquatic organisms. The focus of this study was to investigate the optimum condition to remove residual oil using non-ionic surfactant. The concentration of non-ionic surfactant, mixing time, mixing speed and pH of POME were the parameters that have been analyzed to identify the optimum conditions for removal of residual oil. The optimum conditions for the removal of residual oil was accomplished with a combination of 1.0×10-5 M of Brij 30, 30 minutes of mixing time and 100 rpm of mixing speed at pH 4 of POME. FTIR characterization showed broader absorption of O-H bonding and weak intensity of C-O stretch and C-H stretch in IR spectrum of collected residual oil removed at optimum conditions compared to IR spectra of Brij 30 and POME.